Practical application of product launch for iQue drink and iQue nest - Chew, Sin Yee (2008)
This report illustrates the preparation process of the launch of two new products, namely the iQue Drink and iQue Nest. The students dealt mainly with packaging the products and introducing them into the market via various promotional tools.